Dynamics of Professional and Communicative Tolerance in Educating International Relations Specialists - A. L. Temnitskiy (Vestnik MGIMO-Universiteta)
Under the conditions of the accelerated development of Russian economics, commercial sector and due to a great number of international private companies we can see the intensified problem of tolerance of future diplomats, international specialists, regarding to the system, its the main components such as political, economic, military. It is supposed, that in the modern student environment of future diplomats we can notice the exaltation of values of individual pragmatism and increasing the lack of sociality by deciding of questions about their present and future professional activity. Sociological researches carried out among the students of faculty of international affairs in 2002, 2007 and 2012 review different factors of professional and communicative tolerance. The author of this article markes and diagnoses the materially - pragmatic and art-substantial values of the chosen profession and it's given an interpretation of value orientations content on the categories of employment after the university graduation. Students' estimations define the personal competents of government employee, which are necessary for the successful carrier in the system of MFA of Russia. The interpretation and the real content of communicative tolerance levels are reviewed in the article. The ethnic component of communicative tolerance is studied separately. In conclusion of the article we can define the role of material differentiation of students in the context of communicative tolerance. According to the analyse it is confuted the initial supposition about the glorification of individual pragmatic values and shortage of social responsibility in the student environment. It was found out, that in the communicative tolerance the level of empathy in the personal contact is keeping to be prevalent and stable according to different years of survey. However, it is deduced, the occurred for 10 years the growth of students material welfare didn't contribute to the growth of communicative tolerance. On the whole, data analysis for 10 years of monitoring shows, that the balance of tolerant and intolerant factors regarding the selected profession and communicative practices is keeping to be the same in the student environment.